Biocontrol of Foot and Root Rot Disease of Grasspea (Lathyrus sativus) by Dual Inoculation with Rhizobium and Arbuscular Mycorrhiza (Bangladesh Journal of Microbiology, 2019)
The present study was carried out to evaluate the effect of indigenous arbuscular mycorrhizal fungi (AMF) and Rhizobium (R) on plant growth and their biocontrol against grasspea foot and root rot disease caused by Sclerotium rolfsii. The bio-control potential of these bio-agents against foot and root rot pathogen was carried out under pot culture condition using AMF alone or in combination with rhizobial inoculum in the nethouse of Soil Science Division, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur during 2014-2015 through 2015-2016. The experiment was designed in RCBD with 8 treatments and 4 replications. Grasspea variety BARI Khesari-1 was used as a test crop. Peat based rhizobial inoculum (BARI RLs-10) was used in this experiment @ 50 g kg-1 seed. The AM fungi used in this experiment were Glomus fusianum, Glomus macrocarpum, Glomus warcuppi, Acaulospora foveata, Acaulospora denticulate, Gigaspora albida, Gigaspora rosea, Glomus spp. etc. Soil based AM inoculum containing about approximate 252 spores and infected root pieces of the host plant was used pot-1. There were eight treatments viz. T1: Arbuscular mycorrhiza (AM), T2: Rhizobium, T3: AM + Rhizobium, T4: Sclerotium rolfsii, T5: Sclerotium rolfsii + AM, T6: Sclerotium rolfsii + Rhizobium, T7: Sclerotium rolfsii + AM + Rhizobium and T8: Control. Dual inoculation (AM + Rhizobium) increased 20-25% germination, 50-100% seed yield and 36-98% stover yield compared to control. Dual inoculation reduced 44-48% foot and root rot disease compared to control. On the contrary, Sclerotium rolfsii + Rhizobium, Sclerotium rolfsii + AM, and Sclerotium rolfsii + AM + Rhizobium reduced 12-17%, 16-20% and 28-31% foot and root rot disease, respectively compared to only Sclerotium rolfsii trearment. Therefore, arbuscular mycorrhizal fungal species and its combination with rhizobial inoculum were significant both in the formation and effectiveness of AM symbiosis and the reduction of foot and root rot incidence in grasspea plants. Use of these bio-control agents could be promoted as an active component of bio-intensive Integrated Disease Management Program (IDMP) under organic mode.Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 109-117